2018
DOI: 10.1590/1808-1657000512016
|View full text |Cite
|
Sign up to set email alerts
|

Quality of unprocessed cooled fresh coconut water manually extracted by street vendors

Abstract: Coconut water is a versatile beverage that is rich in nutrients, has few calories, and presents functional and therapeutic characteristics, improving the well-being and health of consumers. However, the growth of deteriorating microorganisms is facilitated by its water activity and high nutrient content; and when combined with improper handling, this product may become a carrier of foodborne diseases. Therefore, the objective of this work was to evaluate the quality of unprocessed cooled fresh coconut water ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
1
1
0
4
Order By: Relevance
“…A similar trend was also reported by Tan et al (2014) who observed changes in characteristics between coconut water aged 5-6 mth and 8-9 mth from the Malayan Tall variety, with total soluble solids values of 5.60 and 6.15, respectively. The titratable acidity levels of the coconut water samples used in the current study were in the range 0.03-0.05 g malic acid per 100 mL sample, which was near the values reported by Soares et al (2017). The value of titratable acidity is expressed as the amount of malic acid because it is the dominant organic acid found in coconut water (Santoso et al, 1996;Tan et al, 2014).…”
Section: Total Soluble Solids Ph Titratable Acidity and Color Values ...supporting
confidence: 73%
“…A similar trend was also reported by Tan et al (2014) who observed changes in characteristics between coconut water aged 5-6 mth and 8-9 mth from the Malayan Tall variety, with total soluble solids values of 5.60 and 6.15, respectively. The titratable acidity levels of the coconut water samples used in the current study were in the range 0.03-0.05 g malic acid per 100 mL sample, which was near the values reported by Soares et al (2017). The value of titratable acidity is expressed as the amount of malic acid because it is the dominant organic acid found in coconut water (Santoso et al, 1996;Tan et al, 2014).…”
Section: Total Soluble Solids Ph Titratable Acidity and Color Values ...supporting
confidence: 73%
“…Resultados do teste de sensibilidade frente aos antimicrobianos de cepas de E. coli isoladas de água de coco ''in natura'' comercializadas no município de Sinop -Mato Grosso Estirpes patogênicas de E. coli encontradas em alimentos são consideradas um problema para a saúde coletiva já que diversas linhagens possuem alto grau de virulência (Who, 2018;Coura et al, 2014). Essa espécie é comensal do trato gastrointestinal de humanos e animais e, quando presentes em alimentos podem ser decorrentes da manipulação insatisfatória do alimento, água contaminada, utensílios mal higienizados (Freitas et al, 2019) e armazenamento inadequado (Soares et al, 2017).…”
Section: Resultsunclassified
“…Do mesmo modo, Serejo et al (2010), avaliando a qualidade da água de coco comercializada por ambulantes da cidade de São Luís, Maranhão, relataram a ausência de coliformes em 100% das amostras analisadas, demonstrando segurança alimentar quanto ao produto avaliado. Soares et al (2017) relata uma análise da qualidade de águas de coco in natura e extraída artesanalmente por comerciantes ambulantes em camelôs no centro de Mossoró, Rio Grande do Norte, onde foi recolhido 12 amostras distintas para coleta e evidenciado a presença do crescimento de coliformes fecais (termotolerantes) em 58,3% das amostras. A existência de bactérias no alimento é notada devido às péssimas condições higiênico-sanitárias e está associada ao manuseio inadequado de alimentos por vendedores ambulantes (Cintra et al, 2017).…”
Section: Amostraunclassified